Preserving I Gede Modara’s “Rotating the Mountain of Mandara Giri” Painting - Mudana, I Wayan; Wirakesuma, I Nengah; Kondra, I Wayan; Sujana, I Wayan; Mustika, I Ketut (International Journal Labs, 2023)
I Gede Modara (1770), nicknamed I Gede Mersadi, was a pioneer of the Kamasan wayang painting, which is now called classical balinese painting. Kamasan wayang paintings are very bound by standards and provisions that are binding and standard, used for offerings and enlightenment to the people. One of the works left by Modara enlightenment painting, entitled